OPTIMALISASI PERANCANGAN APLIKASI MANAJEMEN DATA KOLOMAN, DI DESA PULAU MANDANGIN SAMPANG – MADURA BERBASIS WEBSITE - Fauzan Prasetyo Eka Putra; Siti Ririn Sutarsih; Sofiyulloh Sofiyulloh; Putra Permana; Muhammad Umar Mansyur (LPPM Universitas Abdurrab, 2024)
The rapid development of information technology has had a significant influence on various aspects of life, including data management in traditional activities such as koloman in Pulau Mandangin Village, Sampang, Madura. The manual data management that residents still apply creates difficulties in the process of searching and managing koloman data. This causes the time required to enter and search for information to be longer, and increases the risk of inaccuracies. Additionally, physical storage of information can also pose security and support issues, as information can be lost or damaged. As a result, data management becomes inefficient and people have difficulty finding the information they need quickly and accurately. To overcome these problems, this research proposes an innovative and sustainable solution for designing a web-based koloman data management application. This application is designed to facilitate centralized data processing, automate data input, and provide real-time access to information. Thus, it is hoped that this application can increase the accuracy, speed and transparency of koloman data management, as well as provide significant benefits for the community in managing koloman data more effectively and efficiently. The application of web-based technology also opens up opportunities to increase the capacity of local communities in utilizing information technology.